Factors Impacting Tanzanian Rural and Peri-urban Drug Dispensaries’ Perceived Benefits from Using an mHealth Reporting System - Elias, Alistair; Mtebe, Joel S. (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2020)
This study examines the factors impacting Tanzanian drug dispensaries’ perceptions of the potential benefits of using a mobile health (mHealth) reporting system. Since 2003, the Government of Tanzania has implemented its Accredited Drug Dispensing Outlet (ADDO) programme in support of dispensaries in under-served rural and peri-urban areas. A core element of this ADDO programme is the dispensary use of an mHealth application for reporting on the drugs they are dispensing and the medical conditions that are being treated. This study canvassed the views of ADDO programme dispensaries using the mHealth reporting system in the Iringa, Mbeya, and Njombe Regions, through a survey questionnaire completed by 318 dispensaries and focus group discussions with 38 dispensary personnel. The data revealed that four factors—system quality, information quality, service quality, and price value—are all having a statistically significant impact on dispensaries’ perceptions of the potential benefits of using the mHealth system.
Keywords: mobile health (mHealth), online reporting, drug dispensaries, drug dispensing outlets, information systems, perceived benefits, updated D&M IS success model, extended unified theory of acceptance and use of technology (UTAUT2)¸ system quality, information quality, service quality, facilitating conditions, price value, Accredited Drug Dispensing Outlet (ADDO) programme, Tanzania, Iringa, Mbeya, Njombe